Expectativa de escolarização de crianças cegas após a aquisição do Braille - Cavalcanti, Karina Da Silva [UNIFESP] (2020)
This research aimed to investigate the schooling expectations of those who live with blind children and research the meaning and resignification of Braille, whose presence is considered an indispensable condition for living with the universe of reading and writing. Supported by the theories of Vygotski and Goffman, the importance of looking at the possibilities of the visually impaired person and knowing the prejudices that still permeate the lives of these people was discussed and investigated. To achieve the purpose, the research had as a resource to collect information: interviews, conversation circles, observations and records in text and audio. The analysis of the collected material allowed to identify the expectations of those who live with blind children. It was possible to recognize the expectations often take the place of the child himself, who now has a virtual identity. It was also possible to rescue experiences of schooling / school trajectories (their facilities and difficulties); the intersectionality between disabilities, gender, race and social class and, in the end, produce an inventory of consensus and dissent among teachers, family members, the school community and institutional actors regarding the schooling of blind children who have already learned braille. This was analyzed based on representations of efficiency and application that are directed to those who learn braille.